Urea-based polymethacrylamide purification - Castro,Rafael Theotonio de (2019)
ABSTRACT A purification procedure of polymethacrylamide (PMAm) based on the urea feature of being a powerful Hbond breaker is proposed here. Polymethacrylamide was synthesized in water and the final product presents itself as an insoluble gel what is an obstacle to purification. This physical gel, kept together by numerous interchain H-bonds between amide groups in the polymer, is dismantle by a urea solution (4 mol.L-1) making the polymer soluble. Methanol is then used to precipitate the polymer, keeping urea, water and methacrylamide in the methanolic phase. FTIR, TGA, GPC and HPLC were used to characterize the final product and to prove the efficiency and convenience of this method. The procedure proposed here has presented a good recovery of the polymer and can be considered more convenient, less time-consuming and efficient than others such as dialysis.